Komunikasi Antarpribadi pada Pasangan Suami Istri Muda yang Istrinya Tetap Bekerja - Giovani Anggasta Setiawan (Business Economic, Communication, and Social Sciences (BECOSS) Journal, 2020)
This study aims to be able to find facts and the right way to behave and communicate interpersonally for newly married couples especially for wives who continue to work. This study uses a qualitative descriptive research method that is a study that describes the object of research based on field studies that are able to show the facts. Researchers get data sources through informants or resource persons, namely young couples newly married. Data is divided into 2 namely primary data and secondary data. Primary data through interviews with sources, secondary data through books, internet, & journals. Several previous studies stated that the lower the level of work conflict, the higher the level of marital satisfaction of a couple. The results of this study indicate that the process of interpersonal communication between newly married couples is very important. In this day and age an objection for a wife can still work to be something that is relative / dependent on each individual. There is nothing that determines that a wife works is a wrong thing. Responding to this, there are 3 things that can be done to maintain the quality of communication between the husband and wife, namely: 1. Understand & fulfill their respective roles in the family, 2. Establish the order of priorities for activities that will be the responsibility of the family, 3. Develop a strategy for interpersonal communication after the two agree on what kind of activities will be undertaken during a married life.